Analisis Potensi Daya Saing Ekonomi Kota Jambi - Osrita Hapsara; Sudirman Sudirman (J-MAS (Jurnal Manajemen dan Sains), 2020)
The economic sectors of Jambi City meet 4 criteria. Based on the results of the analysis of the classical Tipologi by using the variable PDRB Jambi city as an analysis area and PDRB of Jambi Province as a reference area resulted in 11 potential economic sectors, 4 backward economic sectors, 1 superior economic sector and potential, 1 sector backward and developing. Potential economic sectors include: industrial processing, procurement of electricity and gas, water procurement, waste management, waste, construction, transportation and warehousing, provision of accommodation and eating, information and communication, real estate, corporate services, government administration, defence and compulsory social security, health services and social activities. The backward economic sectors are: agriculture, forestry, and fisheries, financial services sector and insurance, education services sector, other services. The superior and potential economic sectors are the large and retail sectors; Car repairs. The backward and growing economic sectors are the mining and excavation sectors. Based on the Location Quation sector analysis of the economic sector in Jambi city is: processing industries, electricity and gas procurement, water procurement, waste management, waste, large and retail trade; car repair, construction, transportation and warehousing, provision of accommodation and eating, information and communication, company services, government administration, defence and compulsory social security, health services and social activities. Non-agricultural bases, forestry, and fisheries, mining and excavation, financial services and insurance, education services, other services. Based on the analysis of Incremental Capital Output Ratio (ICOR) The economic sector which has high economic efficiency is mining and excavation, processing industry, construction, large and retail trade; car repair, financial services and insurance, other services. While low economic efficiency is a sector of agriculture, forestry and fisheries.